Performance characteristics according to playing position in elite soccer - Di Salvo, V.; Baron, R.; Tschan, H.; Calderon Montero, F. J.; Bachl, N.; Pigozzi, F. (International Journal of Sports Medicine, 2007)
The paper provides a large-scale study into the motion characteristics of top class soccer players, during match play, according to playing position. Three hundred top-class outfield soccer players were monitored during 20 Spanish Premier League and 10 Champions League games using a computerized match analysis system (Amisco Pro®, Nice, France). Total distance covered in five selected categories of intensity, and the mean percentage of playing time spent in each activity were analyzed according to playing position. Midfield players covered a significantly greater total distance (p < 0.0001) than the groups of defenders and forwards did. Analyzing the different work rates showed significant differences (p < 0.5 - 0.0001) between the different playing positions. There were no significant differences between halves in the total distance covered, or in distances covered at submaximal and maximal intensities. However, significantly more distance was covered in the first half compared to the second in medium intensities (11.1 - 19 km/h). The current findings provide a detailed description of the demands placed on elite soccer players, according to their positional role at different work intensities, which may be helpful in the development of individualized training programs.